PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DENGAN KUALITAS KERJA SEBAGAI MODERATING - Diansyah Diansyah; Niken Dita Dwiyanti (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to examine and analyze the relationship between HRM and job satisfaction and employee performance, with work quality acting as a moderating variable. This study used a sample of 109 respondents who are employees of the North Jakarta Environment Agency. The data collection technique uses a questionnaire survey method and is distributed online using Google, from which it is sent to respondents. The results show that HRM has a significant positive relationship with the performance produced by employees. Job satisfaction has a significant positive relationship with the performance of employees. The quality of work has a significant positive relationship with the performance of an employee. Quality of work is able to weaken the relationship and moderate HRD's impact on an employee's performance. The quality of work is able to strengthen and moderate the relationship between employee satisfaction with their work and employee performance. The research that has been carried out has recommendations aimed at the North Jakarta Environmental Service that want to improve the performance of an employee, so the strategy that can be done is to make employees feel fair, pay according to policy, and give appreciation to employees who have achievements